The hidden (overlooked) impact of living through a pandemic: How parents of children with disabilities fared during COVID-19? - Rakap, Salih; Vural-Batik, Meryem; Kalkan, Sinan; Karnas, Mustafa; Sari, Halil Ibrahim; Bayrakdar, Uygar (Frontiers in Education, 2022)
Children with disabilities and their families are among the most affected populations from the restrictions imposed to prevent the spread of COVID-19 virus, as the special education and rehabilitation services they had been receiving were interrupted.This study investigated the impact of the COVID-19 pandemic on the quality of life of families of children with disabilities and mediating roles of perceived social support,perceived parental self-efficacy,psychological health,psychological resilience,and perceived family burden on this relationship.A correlational survey design was used to collect data from 824 parents of children with disabilities in Turkey.Path analysis was used to examine the direct and indirect effects of COVID-19 on family quality of life. Results indicated that COVID-19 had a significant total effect on family quality of life and perceived social support,parental self-efficacy and psychological resilience had a mediating role on the relationship between impact of the COVID-19 pandemic and family quality of life.Perceived social support was found to the strongest mediator of the relationship between the impact of COVID-19 and the family quality of life, while perceived family burden did not have a statistically significant association with these variables. Family quality of life for children with disabilities decreased as the impact of COVID-19 pandemic increased.Perceived social support,parental self-efficacy and psychological resilience had mediating roles in the relationship between the impact of the COVID-19 pandemic and family quality of life. COVID-19 has resulted in disruption of special education and rehabilitation services for children with disabilities and their families.Changes in daily routines have brought up additional responsibilities to parents of children with disabilities.These additional responsibilities may adversely affect and increase the burden and stress families of children with disabilities experience.High levels of stress in families negatively affect the welfare and quality of life and result in decreased parental attention to support their children.Findings of this study show the mediating link of perceived social support, parental self-efficacy and psychological resilience in the relationship between the impact of the COVID-19 pandemic and family quality of life. Policymakers and service providers should develop and implement specific care actions to support children with disabilities and their families during and after the pandemic.